Analysis of engineering and education student's experiences and expectations on powerpoint usage for instruction. - Ahmed Tajudeen, Shittu; Madarsha, Kamal Basha; Tunku Ahmad, Tunku Badariah; Liman, Mukhtar Alhaji (Institute of Interdisciplinary Business Research, 2011)
This study investigates students’ experiences and expectations in a PowerPoint lecture class. The participants of the study were education and engineering students. A total of 300 questionnaires were administered and 288 were found usable for the study. Frequency, mean, standard deviation and independent sample t-test was used for analyzing the data generated from the study. The findings of the study shows that there is no significant difference in the mean of male and female student experiences and expectations in a PowerPoint lecture class. Also, there is no significance difference in the mean of education and engineering student preferred mode of utilizing the tool for instruction purposes. Base on these findings, the study make suggestions and recommendations on how to improve the quality of instruction that is giving to the present digital native students. The paper also offers implication for education and engineering educators to be cognizance of how to leverage their teaching with technology in order to achieve a meaningful and desire results.